OVERALL EQUIPMENT EFFECTIVENESS DALAM PENINGKATAN KINERJA PRODUKSI BAN PT GOODYEAR INDONESIA - Yusron Rivai; Anas Mitfah Fauzi; Meika Syahbana Rusli (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The objectives of the research are to identify and prioritize issues that affect the performance of the tire production process, give a number of solutions, and map the value stream of the future (future state mapping). One of the tools used to accurately map the current conditions of the production process in lean manufacturing concept is value stream map/VSM. Another measuring instrument used to increase productivity is the overall equipment effectiveness (OEE), which includes time availability, engine performance and quality. From the three variables, it can be seen that the downtime variable has the largest contribution resulting in low value of the OEE. Based on the OEE data, product time change reached 18,8%, and waiting period contributed as much as 4,9% of the total downtime. To reduce the product change time, SMED method (Single Minutes Exchange Dies) is applied at the change of bladder in curing machine, and visual control and poka-yoke applications are also applied to reduce the waiting time. All improvement activities conducted are reflected in the map of the future, including the increase in outputs from the curing machine from 7,814 tires to 8,205 tires per day.Keywords: lean manufacturing, OEE, tire, SMED, map of value chart